Perbedaan Kecenderungan Burnout Ditinjau dari Masa Kerja di Satuan Dalmas Sat Samapta Polresta Kota Yogyakarta - Andri Wijayanto; Arundati Shinta; Femmy Lekahena (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2025)
This study aims to empirically test the differences in burnout in terms of tenure in the Dalmas Unit of Sat Samapta Polresta Yogyakarta City. A total of 74 people were taken as samples with random sample techniques. data collection methods with the Maslach Burnout Inventory (MBI). The results of the difference test using Mann Whitney resulted in a Mann Whitney U value of 946.5 with a significance of 0004. i.e. there is a significant difference in burnout in police officers serving in the Dalmas Unit of Sat Samapta Polresta Yogyakarta City with a service period of < 3 years and ≥ 3 years. Descriptive statistical tests on burnout with a tenure of < 3 years show an average of 62.63. Meanwhile, the work period ≥ 3 years shows an average of 68.47. This shows that burnout in police officers serving in the Dalmas Unit of Sat Samapta Polresta Yogyakarta City with a work period of ≥ 3 years experiences higher burnout than those with a work period of < 3 years.